TREN PRAKTIK STUDY DATE DI PERPUSTAKAAN SEBAGAI FENOMENA SOSIAL BARU PENGGUNA: ANALISIS BIBLIOMETRIK - Tiara Rizki Mahendra (Pustakaloka, 2026)
The "study date" phenomenon has emerged alongside shifting study patterns in the digital era and the rise of collaborative learning practices in public spaces, including libraries. However, scholarly inquiry into this phenomenon from a library and information science perspective remains relatively limited, particularly regarding the link between study dates and information-seeking behavior. This study aims to examine the evolution of academic literature on the study date phenomenon through the lens of information-seeking behavior in library science. A bibliometric analysis was conducted on Scopus-indexed publications from 2016 to 2025 using the search query ("study date" AND "information seeking behavior"). Following the search and screening process, 384 documents were analyzed to map publication trends, dominant keywords, national contributions, and research themes. The findings indicate that while research on study dates in the context of information-seeking behavior is still limited, it reveals strong connections to aspects of information-seeking behavior, social interaction, and user psychological factors. Furthermore, the subject remains underexplored in the field of library and information science, thereby presenting opportunities for future research.